Desarrollo de un sistema de trazabilidad en el proceso de elaboración de balanceados para pollos en la etapa de crecimiento en la “Avícola el paraíso” - Quille Guambuguete, Lady Yajaira (2025)
The objective of this study was to develop a traceability system for the feed production process for poultry in the growth stage at the company “Avícola El Paraíso,” in accordance with ISO 22005:2011. Initially, a diagnostic assessment of the current production process was conducted, revealing multiple deficiencies related to traceability, including lack of documentation, limited staff training, inadequate machinery maintenance, absence of signage, and infrastructure shortcomings. Based on this diagnosis, a traceability system tailored to the company's needs was designed and formalized in a technical manual outlining responsibilities, procedures, records, and monitoring mechanisms to ensure the safety and quality of the feed. In addition, a flow diagram of the production process was developed, a practical traceability exercise was implemented, and a proximal analysis of the final product was conducted, allowing for the creation of a label compliant with INEN 1829:2014. The nutritional results of the feed showed appropriate levels of protein (24.31%), fiber (9.27%), moisture (10.22%), and ash (5.53%); however, the fat content (3.25%) was below the minimum required threshold (6%). The proposed system enhances efficiency, strengthens control at each stage of the process, and improves the company’s capacity to respond to incidents in a timely manner. Finally, opportunities were identified to position the company within the local market, aiming to consolidate its competitiveness and long-term sustainability.